Luminescent multifunctional biocellulose membranes - Caiut, J. M A; Barud, H. S. [UNESP]; Santos, M. V. [UNESP]; Oliveira, U. L.; Menezes, J. F S; Messaddeq, Younes [UNESP]; Ribeiro, Sidney José Lima [UNESP] (SPIE, the international society for optics and photonics, 2011)
Luminescent biocellulose membranes were obtained by incorporation of ethanolic solutions of the europium compounds [Eu(BTFAC)3(H2O)2], [Eu(BTFA) 3(DBSO)2], [Eu(BTFA)3(PTSO)2] and [Eu(BTFA)3(FSO)2] (BTFAC- 4,4,4-Trifluoro-1- phenyl-1,3-butanedione DBSO- dibenzyl sulfoxide, PTSO- p-Tolyl sulfoxide and FSO- phenyl sulfoxide). Selfsustainable semi-transparent composite membranes were obtained showing strong emission under UV exctiation. The antenna hole played by the ligands was observed to be more efficient in the composite membranes than in the precursor complexes which by themselves are also strong red emitter compounds. These new multifuctional membranes could find application in different areas as phosphors and UV→Visible energy converting devices. © 2011 Copyright Society of Photo-Optical Instrumentation Engineers (SPIE).
Keywords: β-diketonates; biocellulose; europium; luminescent membranes; sulfoxides; Biocellulose; Ethanolic solution; P-tolyl; Precursor complexes; Red emitter; Self-sustainable; Semi-transparent; Europium; Europium compounds; Luminescence; Membranes; Thin films; Composite membranes